The Mausoleum at Halicarnassus - Dinsmoor, William (Analecta Gorgiana, 2009)
Dinsmoor suggests a reconstruction of the fragmented Mausoleum of Halicarnassus, one of the wonders of the ancient world and a model for several modern monuments